Efektivitas Ekstrak Buah Dan Daun Belimbing WuluhUntuk Mencegah Kontaminasi Pada Pertumbuhan BijiKacang Hijau Secara In Vitro - Hussniah, Salissatul; , Triastuti Rahayu, S. Si, M.Si (2016)
The main problem in the plant propagation techniques of plant tissue culture is contamination by bacteria or fungi. to overcome these contaminants it is often used Plant Preservative Mixture (PPM) as an antimicrobial. Bilimbi's fruit and leaf contain oxalic compounds of phenols, flavonoids, tannins, sulfur, and formic acid containing many benefits, one of them can be antibacterial. The purpose of this researcing to determine the effectiveness extract of the bilimni's fruit and leaves to prevent contaminants on germination seed of mung bean in vitro. This reaseach design is completely randomized design with two factors: a factor of 1: Bilimbi's fruit (E1); Bilimbi's leaves (E2) and factor 2: extract concentration of 15% (K2); extract concentration of 30% (K3). Extraction of bilimbi's fruit and leaves done infundation method using solvent water (1:10) solvent water temperature must reach a temperature of 900C for 15 minutes with the help waterbath. The parameters observed during 5 days of the mung beans are the percentage of bottles are not contaminants, plant height, roots, leaves and sprouts conditions. Differences planting medium are bilimbi's fruit extracts, bilimbi's leaf extracts, and negative control and positive control from the medium not effective against amount mung beans leaves. Bilimbi's leaf extract 15 % concentration effective topreventing contaminants 70% on mung bean's seed germination by in vitro.